PERMAINAN TRADISIONAL TERHADAP PENDIDIKAN PERKEMBANGAN MOTORIK KASAR ANAK PADA DISIBILITAS TUNAGRAHITA - Dwi Manna Nasmi Dzakiyyah; Sumaryanti; Bernadeta Suhartini; Eka Swasta Budiyanti (Jurnal Tunas Pendidikan, 2024)
Gross motor development in children is an important role for the progress of their movement skills and physical activities. Gross motor development is one of the important aspects that teachers and parents should pay attention to. Children who have good gross motor skills will be more flexible in mingling with their friends. This of course will affect the child's confidence when socializing with their friends. But not for those with disabilities. Grahita disabilities have problems related to gross motor, namely balance, coordination, body movement, muscle and bone strength and gross motor abilities of children with grahita disabilities can be associated with many physical activities. One of the physical activities is traditional games. This type of research uses a literature study in writing to review literature through various journals, theoretical references that are relevant to the research topic. The impact of traditional games on gross motor skills of children with disabilities is the main topic studied in this study. Based on the findings of the review, it can be concluded that traditional game activities have a significant important role in the gross motor development of children with disabilities. Various studies have shown that through traditional games, children with disabilities can experience improvements in gross motor skills, including aspects of balance, coordination, body movement, muscle strength, and other gross motor abilities.